2022
DOI: 10.1002/vetr.2343
|View full text |Cite
|
Sign up to set email alerts
|

Surveying dog owners' use and understanding of, and communication with veterinarians about, complementary and alternative veterinary medicine

Abstract: Background: Complementary and alternative veterinary medicine (CAVM) seems to be gaining acceptance by pet owners. Client-veterinarian communication about CAVM is important to explore client perceptions and facilitate open exchange of ideas between owners and veterinarians. Methods: This study includes an online, cross-sectional survey of dog owners to evaluate CAVM use and client-veterinarian communication about CAVM. Based on the extended theory of planned behaviour, factors influencing the intention to use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(18 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…The majority of participants indicated that CAVM use sometimes happens without disclosure to the veterinarian. Although it should be kept in mind that this was only based on the disclosure estimated by the participating veterinarians, high non‐disclosure rates have already been described in previous studies surveying horse owners 6–8,10 . In a questionnaire study in horse owners conducted by Thirkell and Hyland, the majority of participants (81%) indicated that they would try new therapies disregarding the veterinarian's opinion about CAVM 5 .…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The majority of participants indicated that CAVM use sometimes happens without disclosure to the veterinarian. Although it should be kept in mind that this was only based on the disclosure estimated by the participating veterinarians, high non‐disclosure rates have already been described in previous studies surveying horse owners 6–8,10 . In a questionnaire study in horse owners conducted by Thirkell and Hyland, the majority of participants (81%) indicated that they would try new therapies disregarding the veterinarian's opinion about CAVM 5 .…”
Section: Discussionmentioning
confidence: 97%
“…Participants of the current study mainly suggested CAVM modalities to clients as a possible treatment based on a diagnosed problem or disease. However, animal owners generally view CAVM more as a method to improve general well‐being, chronic disease or a last resort in case of failure of traditional veterinary medicine 6,10 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations